Associations Between Health Literacy and Health Behaviors Among Urban High School Students. (2nd November 2017) - Park, Aesoon; Eckert, Tanya L.; Zaso, Michelle J.; Scott‐Sheldon, Lori A. J.; Vanable, Peter A.; Carey, Kate B.; Ewart, Craig K.; Carey, Michael P.
ABSTRACT: BACKGROUND: Health literacy is crucial to develop health‐related knowledge, adopt healthy lifestyles, and benefit from health care services. However, research on the association between health literacy and adolescent health outcomes, particularly on their prospective associations, is rare. We assessed health literacy using 3 validated measures, and examined cross‐sectional and prospective associations between health literacy and adolescent health behaviors and outcomes. METHODS: We conducted a short‐term prospective study of 250 adolescents (mean age = 14 years; 57% female; 48% African American) who were entering or in the ninth grade in an urban school district. Health literacy was assessed by individual interviews at baseline, and health‐related behaviors and outcomes were assessed by a paper‐and‐pencil survey at baseline and at a 6‐month follow‐up. RESULTS: Nearly half of the sample was reading at least 2 grades below expected levels. Lower baseline health literacy was associated with a lower self‐rating of general health, unhealthier diet, heavier weight, and greater engagement in problem behaviors and sexual behaviors at baseline. Lower baseline health literacy also was associated with a greater increase in substance use over time. CONCLUSIONS: Results point to the pressing need to improve health literacy in urban high school students.